A New Perspective in the Field of Cardiac Safety Testing through the Comprehensive In Vitro Proarrhythmia Assay Paradigm. (January 2016) - Fermini, Bernard; Hancox, Jules C.; Abi-Gerges, Najah; Bridgland-Taylor, Matthew; Chaudhary, Khuram W.; Colatsky, Thomas; Correll, Krystle; Crumb, William; Damiano, Bruce; Erdemli, Gul; Gintant, Gary; Imredy, John; et al.
For the past decade, cardiac safety screening to evaluate the propensity of drugs to produce QT interval prolongation and Torsades de Pointes (TdP) arrhythmia has been conducted according to ICH S7B and ICH E14 guidelines. Central to the existing approach are hERG channel assays and in vivo QT measurements. Although effective, the present paradigm carries a risk of unnecessary compound attrition and high cost, especially when considering costly thorough QT (TQT) studies conducted later in drug development. TheC omprehensiveI n VitroP roarrhythmiaA ssay (CiPA) initiative is a public-private collaboration with the aim of updating the existing cardiac safety testing paradigm to better evaluate arrhythmia risk and remove the need for TQT studies. It is hoped that CiPA will produce a standardized ion channel assay approach, incorporating defined tests against major cardiac ion channels, the results of which then inform evaluation of proarrhythmic actions in silico, using human ventricular action potential reconstructions. Results are then to be confirmed using human (stem cell–derived) cardiomyocytes. This perspective article reviews the rationale, progress of, and challenges for the CiPA initiative, if this new paradigm is to replace existing practice and, in time, lead to improved and widely accepted cardiac safety testing guidelines.